"Male Gaze" or "Power of Display"? Love, Conjugality and Gender in Bridal-Gown Photography in Contemporary Rural China. Issue 4 (20th October 2022) - Hou, Renyou
Abstract : Based on ethnographic fieldwork in a Chinese village and at a wedding planning company, this article analyzes the matrimonial norms and practices, as well as the representation of gender relations, in contemporary rural China. I argue that even though for mass consumption the bridal-gown photography still enables young villagers to have an extraordinary experience that promotes expression of their personal desires. By examining the mise en scène of photographed protagonists, I conclude that the gender relations cannot simply be viewed as male domination, but rather as a more complex hierarchical relationship with a possibility of reversal of power and authority positions in family and social life.